Entomología - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
In 1980 major studies on entomology were directed to accumulating information on the complex of insects that attack the cassava crop, emphasizing biological control studies of important pests, especially Erinnyis ello and Phenacoccus sp. Basic studies on the stemborer (Chilomina clarkei) were conducted for the 1st time and a new pest, a subterranean Hemiptera (Cyrtomenus bergi) which causes considerable damage to cassava roots, is described. Three trials were conducted at the Nataima station of the Instituto Colombiano Agopecuario to determine losses from whitefly (Aleurotrachelus socialis) infestations. It was found that when whiteflies were not controlled, av. yields decreased from 26 to 9 t/ha. Nutritional habits, insect biology, and biological control of the mites Mononychellus tanajoa, M. urticae, and Oligonychus peruvianus were studied. The germplasm bank at the Centro Internacional de Agricultura Tropical was evaluated for resistance to the cassava lacebug (Vatiga manihotae); of the 1865 fines tested, 527 (28 percent) were scored less than 1 on a 0-5 damage scale. (CIAT)